The use of whole-body cryostimulation to improve the quality of sleep in athletes during high level standard competitions - Bouzigon, R.; Ravier, G.; Dugue, B.; Grappe, F. (British Journal of Sports Medicine, 2014)
Background: This is a field study realized during basketball preparation tournaments for the European championship 2013 with men and women French team. During these competitions, athletes used Whole-Body Cryostimulation (WBC) exposures to enhance their recovery. Objective: The aim of this work was to investigate the effects of WBC on the quality of sleep (QS) in athletes during the night following the exposure. Design: The preparation took place during one week in a training camp followed by three international matches in three days (one per day).Setting The study was performed with high standard level athletes men and women of the basketball French teams. Participants 27 basketball players participated fully in the study (12 females, 11 males, age: 25.8±3.5 years; weight: 88.5±15.7 kg; height: 192.5±11.8 cm). Risk factor assessment: The WBC treatment was 3-min exposure between -110°C and -150°C in the morning or/and in the evening after a training or match session.Main outcome measurements The QS was assessed every day before the exposure with a perceptual scale graduated from 1 "bad sleep" to 5 "restful sleep" adapted from Spiegel's questionnaire. The data were analyzed using paired t-test. Results: An improvement in the QS was observed in the night following WBC (3.7±0.7 vs 3.2±0.9, P<.05) compared with what was observed the night without previous WBC.Conclusions Athletes experienced better sleep quality after WBC exposure. Even if the night duration was short during this period, they expressed they had a deeper, quieter and less disturbed sleep. The improvement of the QS during both competition and heavy training load periods appears of importance to enhance athletes' recovery. Such situation may lead to 1) a better standing of the training load, 2) less fatigue before the matches and 3) a decrease of the injury risks.